2017
DOI: 10.3390/en10111887
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Clay-Abundant Shale Formations: Use of CO2 for Production Enhancement

Abstract: Clay-abundant shale formations are quite common worldwide shale plays. This particular type of shale play has unique physico-chemical characteristics and therefore responds uniquely to the gas storage and production process. Clay minerals have huge surface areas due to prevailing laminated structures, and the deficiency in positive charges in the combination of tetrahedral and octahedral sheets in clay minerals produces strong cation exchange capacities (CECs), all of which factors create huge gas storage capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 104 publications
1
16
0
Order By: Relevance
“…With increasing shale content, the porosity of sand‐packs decreased and reached the minimum level of 26% for SP‐6 exhibiting 75% sand and 25% shale (Table ). Our results indicate that shale's inclusion has caused a marked decrease in the porosity of sand‐pack, which was also demonstrated by Zhang et al, who concluded that the impact of increased swelling in shale is connected with blockage of free space in porous formations that in turn probably makes the sand‐pack less porous and decreases porosity. Thus, the shale, made up of primarily fine grains, occupies the interstitial space inside the sand‐pack during mixing and ramming.…”
Section: Resultssupporting
confidence: 87%
“…With increasing shale content, the porosity of sand‐packs decreased and reached the minimum level of 26% for SP‐6 exhibiting 75% sand and 25% shale (Table ). Our results indicate that shale's inclusion has caused a marked decrease in the porosity of sand‐pack, which was also demonstrated by Zhang et al, who concluded that the impact of increased swelling in shale is connected with blockage of free space in porous formations that in turn probably makes the sand‐pack less porous and decreases porosity. Thus, the shale, made up of primarily fine grains, occupies the interstitial space inside the sand‐pack during mixing and ramming.…”
Section: Resultssupporting
confidence: 87%
“…The commercial development of shale gas has been driven by three key advances in technology and science: (1) horizontal well plus multi-stage hydraulic fracturing [1][2][3][4][5][6], (2) the understanding of gas storage mechanisms [1], and (3) the understanding of multi-scale mechanisms of gas flows from shale matrix to hydraulic fracture [7][8][9][10]. A shale gas reservoir has free gas stored in matrix pores and natural fractures, and adsorbed gas on the organic matter [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an understanding of the total fracturing fluid leak-off rate is one of the most important indices in fracturing design using CO 2 , especially in relation to the total volume or weight of fracturing fluids. The permeability of shale matrix to water is valued 22.10 nD which is measured in Section 5 at 16 MPa injection pressure, and the permeability to liquid CO 2 is valued at the same injection pressure at room temperature, according to Equations (7) and (8), the ratio of the leak-off rate in volume of CO 2 and water is around 14.03, and the ratio in weight is around 12.62. With the increase of penetration distance, the penetration distance of CO 2 is much higher than that of water due to lower viscosity, and a lower pressure gradient for CO 2 injection can reduce its leak-off rate, which indicates that the ratio of the leak-off rate between CO 2 and water is over-valued.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…The imbibition of water into the shale matrix easily causes a blocking effect in tiny pore throats, which closes the channels for gas transport from the shale matrix to the created fractures [6]. The formation damage caused by injected water is more serious in clay-abundant shale formations, because the interaction between water and clay minerals can induce the swelling of clay minerals, which further reduces the porosity of pores and fractures [7]. In the light of other environmental concerns caused by water-based fracturing fluids, such as large water consumption and wastewater generation [8], hydraulic fracturing have been banned legislatively in some countries [9].…”
Section: Introductionmentioning
confidence: 99%